Vlijanie raznych metodov aerobnoj trenirovki na arterial'noe davlenie, žirovuju massu i tolšcinu myšc sportsmenov silovych vidov sporta: randomizirovannoe kontroliruemoe issledovanie - Miroshnikov, A. B. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
he study answers the question: what method of aerobic work has a greater effect on muscle thickness, body fat mass, oxygen consumption and blood pressure in hypertensive athletes of power sports. The study involved male athletes aged 31.2 ± 4.5 years. To achieve this goal, the following methods were used: examination, questioning, triple measurement of blood pressure, bioimpedance analysis, ergospirometry, ultrasonographic measurements of the thickness of the quadriceps femoris and methods of mathematical statistics. The result of the study was a significant increase in the thickness of the working muscles and the maximum oxygen consumption in the intervention groups, as well as a decrease in fat mass and blood pressure. Despite similar advantages in cardiac rehabilitation, interval work required 38% less time, which could significantly affect adherence to such an activity that is not specific to this sport and the screening of participants in long-term rehabilitation.